The Macroeconomics of De-Cashing - Kireyev, Alexei (IMF Working Papers; Working Paper ;, 2017)
The paper presents a simple framework for the analysis of the macroeconomic implications of de-cashing. Defined as replacing paper currency with convertible deposits, de-cashing would affect all key macroeconomic sectors. The overall macreconomic impact of de-cashing would depend on the balance of growth-enhancing and growth-constraining factors. Starting from a traditional saving-investment balance, the paper develops a four-sector macroeconomic framework. It is purely illustrative and is designed to provide a roadmap for a systematic evaluation of de-cashing. The framework is disaggregated into the real, fiscal, monetary, and external sectors and potential implications of de-cashing are then identified in each sector. Finally, the paper draws a balance on possible positive and negative macroeconomic implications of de-cashing, and proposes policies capable of augmenting its economic and social benefits, while reducing potential costs.